Response of foliar mineral nutrients to long‐term nitrogen and phosphorus addition in a tropical forest. (5th September 2021) - Mo, Qifeng; Wang, Wenjuan; Lambers, Hans; Chen, Yiqun; Yu, Shiqin; Wu, Chunsheng; Fan, Yingxu; Zhou, Qing; Li, Zhi'an; Wang, Faming
Abstract: Mineral nutrients play a pivotal role in plant growth, development and reproduction. The uptake and distribution of nutrients are generally limited by soil nutrient availability, affected by global change. However, the responses of foliar mineral nutrient concentrations to changes in soil nutrient availability remain largely untested in tropical forests. We used a field‐based experiment with nitrogen (N) and phosphorus (P) addition in a tropical forest in southern China to investigate the effect of N and P fertilization on exchangeable soil and foliar mineral nutrients of five understorey species. Our results show that N addition did not change soil pH, but reduced exchangeable soil Ca 2+, Mg 2+, Zn 2+, Fe 3+ and Mn 2+ concentrations. In contrast, P addition increased soil pH, while it had no effects on exchangeable cations. Nitrogen addition significantly decreased foliar [Ca], [Mg] and [Mn], while P addition markedly reduced foliar [Cu] for most of the studied species. Foliar [K] and [Fe] were not affected by fertilization. The results indicate that long‐term N addition reduced the concentrations of several mineral nutrients in leaves, and we did not observe any adaptive mechanisms (e.g. increased transpiration to take up mobile soil nutrients) in the studied species to maintain foliar nutrient concentrations at high N supply. Synthesis . The responses of other foliar nutrient concentrations to N and P co‐addition were more complicated than those of N and/or P, and the specific decreases in mineral nutrient concentrations following long‐term N addition may influence key physiological process in the studied tropical understorey species, and ultimately reduce their fitness and survival under high N deposition. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 摘要: 矿质养分在植物生长、发育和繁殖过程中扮演着关键的角色。一般来说, 植物对矿质元素的吸收和分配受到土壤养分有效性的限制, 同时也受到全球变化的影响。但是, 热带森林植物叶片矿质养分含量对土壤养分有效性变化的响应尚不清楚。 在华南地区, 我们利用热带森林氮磷添加的野外试验来探究长期氮磷施肥对土壤可交换性离子和5种林下物种叶片矿质养分含量的影响。 我们的结果表明, 氮添加并没有改变土壤pH值, 但降低了土壤可交换的Ca 2+, Mg 2+, Zn 2+, Fe 3+, 和Mn 2+ 含量。相反, 磷添加提高了土壤pH值, 但对土壤可交换性阳离子没有影响。氮添加显著降低了叶片的钙、镁和锰含量, 而磷添加降低了大多数物种叶片的铜含量。叶片的钾和铁含量并没有受到施肥处理的影响。 这些结果表明, 长期的氮添加降低了叶片中钙、镁等矿质元素的含量, 而我们并没有观测到这些物种形成任何的适应机制 (比如, 通过提高蒸腾作用来获取更多的可移动的矿质养分) 来维持高氮输入下植物叶片的矿质养分含量的稳定。通过本研究, 我们发现叶片矿质元素对氮磷添加的响应要比氮磷含量的响应更为复杂, 长期氮添加降低矿质元素含量可能会影响到热带森林林下物种关键的生理过程, 最终将降低这些物种在高氮沉降背景下的适应性和生存能力。